2021
DOI: 10.1002/nop2.1007
|View full text |Cite
|
Sign up to set email alerts
|

Disease acceptance and social support in patients with peripheral vascular diseases treated in the surgical ward

Abstract: Each surgery is an emotional stimulus associated with fear of its consequences . The scar after a surgery makes a physical, emotional and psychological mark with symptoms of depression, anxiety, anger and post-traumatic stress (Ngaage & Agius, 2018). Surgical treatment, however justified, is an interference with the physical integrity of the patient. The closer to the procedure, the more the patient considers the dangers arising from it. The patient's mental state becomes changeable, hope appears, but also anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(79 reference statements)
0
4
0
Order By: Relevance
“… 94 , 95 Social support by family members, close relatives, nurses, and caregivers may have an impact on disease acceptance and cooperation; it may give individuals the sense that they are cared for. 96 For example, good social support may contribute to better recovery following bypass surgery in PAD patients. 97 In addition, social support can help mitigate the depressive symptoms that are prevalent in patients with PAD.…”
Section: Impact Of Sdohs On Patients With Padmentioning
confidence: 99%
“… 94 , 95 Social support by family members, close relatives, nurses, and caregivers may have an impact on disease acceptance and cooperation; it may give individuals the sense that they are cared for. 96 For example, good social support may contribute to better recovery following bypass surgery in PAD patients. 97 In addition, social support can help mitigate the depressive symptoms that are prevalent in patients with PAD.…”
Section: Impact Of Sdohs On Patients With Padmentioning
confidence: 99%
“…Autonomy support from healthcare providers was defined as encouraging patients to perform or adhere to a recommended behaviour, leading to a supportive relationship between patients and their healthcare providers (Czarnecka et al, 2021). We used the healthcare climate questionnaire developed by Williams et al (1996), translated and validated into Korean by Seo (2008).…”
Section: Autonomy Support From Healthcare Providersmentioning
confidence: 99%
“…Several reviews have reported that lifestyle modification, including smoking cessation, regular exercise and antiplatelet therapy in PAD patients is critical for improving quality of life and avoiding adverse health outcomes (Abola et al, 2020; Chen et al, 2019). Despite the advantages of optimal self‐management, it is often neglected by PAD patients (Abaraogu et al, 2018; Czarnecka et al, 2021). Specifically, patients who underwent revascularization are less likely to participate in self‐management because a successful procedure can dramatically relieve symptoms such as intermittent claudication and resting pain (DiGiacomo et al, 2021; Saxon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation